Etika Organisasi: Upaya Penumbuhan Komitmen - Soegijo, Ivor Hubertus; Mulya, Teguh Wijaya; Mawardi, Artiawati (Faculty of Psychology, Universitas Surabaya, 2007)
All too often, tobacco producing companies, experience problems concerning deceitfulnes committed by farmers as working partners. To alleviate such, a connecting person called field force was established. The application of ethics in working relations between the field forces and farmers have improved their working commitment. This research explored the needs to build ethics and how it could be reached. In this explorative qualitative approach, interviews and observations were conduc- ted on the manager, four field forces, and four farmers. Success of ethical application in organisation could be influenced by spitituality, cultural background, and life experience. The existence of ethics within organisation could enhance the working commitment of workers and partners in working. Commitments enhance activity and productivity, minimizing fraud in organisation, and minimizing the effects of negative career entrenchment. Perusahaan yang bergerak di bidang tembakau banyak mengalami masalah yang berkaitan dengan kecurangan dari mitra kerja (petani). Untuk mengatasi itu dibentuklah tenaga penghubung la- pangan yang dijuluki field force. Penerapan etika dalam relasi kerja tenaga lapangan dan petani telah menumbuhkan komitmen dalam bekerja. Penelitian ini berusaha mengeksplorasi apa yang diperlukan untuk membangun etika dan bagaimana cara melakukannya. Dalam penelitian kualitatif eksploratif ini dilakukan wawancara dan observasi pada manajer, empat orang tenaga lapangan, dan empat orang petani. Keberhasilan penerapan etika dalam organisasi dapat dipengaruhi oleh spiritualitas, latar bela- kang budaya, dan pengalaman hidup. Adanya etika dalam organisasi dapat meningkatkan komitmen para field force sebagai penghubung dan para petani sebagai mitra kerja dalam bekerja. Komitmen meningkatkan kinerja dan produktivitas karyawan, mengurangi kecurangan dalam organisasi, serta mengurangi dampak negatif career entrenchment.